2022
DOI: 10.1038/s41467-022-32419-5
|View full text |Cite
|
Sign up to set email alerts
|

Nested order-disorder framework containing a crystalline matrix with self-filled amorphous-like innards

Abstract: Solids can be generally categorized by their structures into crystalline and amorphous states with different interactions among atoms dictating their properties. Crystalline-amorphous hybrid structures, combining the advantages of both ordered and disordered components, present a promising opportunity to design materials with emergent collective properties. Hybridization of crystalline and amorphous structures at the sublattice level with long-range periodicity has been rarely observed. Here, we report a neste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 64 publications
(53 reference statements)
2
27
0
Order By: Relevance
“…This role of VEGF is conceptually similar to the classical case of EGF induced Notch signaling in C. elegance vulva development (25,26). On the other hand, our results also suggest that an increase of VEGF levels can introduce disorder into this pattern, similar to order-disorder transition for various composite materials (12,13), which may occur with increasing temperature and have the properties of a sharp phase transition. More specifically, high VEGF levels may play the role similar to an increased temperature in order-disorder transitions, leading to emergence of partially disordered 'salt-andpepper 'structures.…”
Section: Discussionsupporting
confidence: 78%
“…This role of VEGF is conceptually similar to the classical case of EGF induced Notch signaling in C. elegance vulva development (25,26). On the other hand, our results also suggest that an increase of VEGF levels can introduce disorder into this pattern, similar to order-disorder transition for various composite materials (12,13), which may occur with increasing temperature and have the properties of a sharp phase transition. More specifically, high VEGF levels may play the role similar to an increased temperature in order-disorder transitions, leading to emergence of partially disordered 'salt-andpepper 'structures.…”
Section: Discussionsupporting
confidence: 78%
“…In the last few decades, increasing numbers of research on MHPs under high pressure have been reported, adding numerous new structures with novel physical properties to the family of perovskite materials. In inorganic MHPs, for instance, CsPbI 3 and CsPbBr 3 have been reported to undergo the conversion from the Pm m perovskite structure with corner-shared BX 6 octahedra to the Pnma structure with double chains of edge-shared PbX 6 under pressure; , 2D CsPb 2 X 5 (X = Br and I) with face-shared BX 6 octahedra (space group I 4/ mcm ) was synthesized by the direct phase separation of 1D CsPbI 3 with edge-shared PbX 6 octahedra (space group C 2/ m ) at high-pressure and temperature ( P – T ) conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Chemical methods including ion doping and molecular engineering have shown their capability in preparing hybrid heterostructures with designed interfaces (17)(18)(19), whereas a new sample needs to be synthesized for each band state, and the energy level cannot be continuously and precisely controlled (usually with the energy step over 0.1 eV) (15,16,20,21). As a thermodynamic parameter, pressure can effectively modify the lattice and electronic structures to realize diverse states in a single material (22)(23)(24)(25)(26)(27)(28). Thus, applying high pressure on these HSHs enables the tuning of their interfacial electronic structures and the band alignment in a controlled manner, where the building blocks of HSHs have different responses to pressure (29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%